(untitled) (Fiep Bulletin - online, 2014)
This paper offers an overview of Physical Education in Canada, considering the specific political characteristics of thirteen different province government administrations. Every province features a public system, an independent school system, a parochial system and several school districts within each system. That is the reason why there are several approaches for Physical Education in Canada. Those approaches started in 1981 with the Columbia Secondary British Curriculum, and went on moving in the 90s along several schools such as Calgary, Manitoba, Vitoria and others. An article published by CAHPERD was a great contribution to the debate about curricula. The article shows the differences about the different conceptions. Currently there are several Websites which evidence those specific Physical Education concepts. Each one of them is directly related to the provinces where those Websites schools are located. The author concludes by mentioning how difficult it is to make an analysis of Physical Education in Canada, due to its variation. However, all the conceptions lead to the development of a healthy lifestyle provided they follow processes which emphasize knowledge, skills and attitudes.